A brief cognitive behavioural preimplantation and rehabilitation programme for patients receiving an implantable cardioverter-defibrillator improves physical health and reduces psychological morbidity and unplanned readmissions. Issue 1 (10th December 2007) - Lewin, R J; Coulton, S; Frizelle, D J; Kaye, G; Cox, H
Abstract : Objective: To assess the clinical and cost effectiveness of a brief home-based cognitive behavioural rehabilitation programme (the ICD Plan) for patients undergoing implantation of a cardiac defibrillator. Design: A prospective multicentred, intention-to-treat, cluster-randomised controlled trial. Setting: Eight implantable cardioverter-defibrillator (ICD) implantation centres in the UK. Patients: Consecutive series of patients undergoing implantation with an ICD. Interventions: The control group received usual care and advice from an experienced healthcare professional. The intervention group received usual care plus the ICD Plan. The plan was introduced before implantation, with three further brief telephone contacts with the nurse over the next 12 weeks. Main outcome measures: Health-related quality of life (Short Form Health Survey (SF-12)), anxiety and depression (Hospital Anxiety and Depression Scale (HADS)), activity limitations (subscale from the Seattle Angina Questionnaire (SAQ)), unplanned admissions and other economic data using a questionnaire developed for the study. Results: 192 patients were recruited to the study (71 intervention, 121 control). At 6 months after surgery the intervention group had better physical health (37.83 vs 34.24; p<0.01), fewer limitations in physical activity (34.02 vs 31.72; p = 0.04), a greater reduction in the proportion of patients with a borderline diagnosis of anxiety (21% vs 13%; p = 0.60) and depression (13% vs 2%; p = 0.30), more planned ECGs (89% vs 66%; p = 0.04) and 50% fewer unplanned admissions (11% vs 22%; p<0.01). Conclusions: The ICD Plan improved health-related quality of life, reduced the incidence of clinically significant psychological distress and significantly reduced unplanned readmissions. It is a cost effective and easily implemented method for delivering rehabilitation and psychological care to patients undergoing ICD implantation. Trial registration number: ISRCTN70212111.